PERFORMANSI MESIN DIESEL MENGGUNAKAN BIODIESEL DARI CAMPURAN BIJI KARET-MINYAK PIROLISIS LIMBAH PLASTIK-MINYAK SOLAR - Sitorus, Tulus Burhanuddin; Tambunan , Bisrul Hapis; Sihombing , Hendrik Voice; Ambarita, Himsar (Jurnal Rekayasa Mesin, 2025)
This research examines the performance of a Diesel engine that uses alternative fuel biodiesel from a mixture of rubber seeds with plastic waste pyrolysis and diesel oil. The plastic waste used is plastic bottle caps, which are processed by pyrolysis to obtain oil. One of the objectives of mixing biodiesel with plastic waste pyrolysis oil is to increase the calorific value of rubber seed biodiesel. The calorific value of rubber seed biodiesel is 39.95 kJ/kg, and the calorific value of plastic waste pyrolysis oil is 46.55 kJ/kg. Mixing rubber seed biodiesel with plastic waste pyrolysis oil increases the calorific value of rubber seed biodiesel by around 9.63%-13.63%. Experimental results show that there is a reduction in exhaust emissions when using biodiesel for opacity of 7.51-66.08%, CO 12.5-50%, HC 7.14-62.96% and an increase in CO2 emissions of around 3.08-84.62%. Tests using biodiesel were carried out without modifying the Diesel engine.